Sistem Informasi Laboratorium Klinik Berbasis Client Server - Umar, Rusydi; Siswanto, Anwar; Abe, Tuska; Lestari, Tri; Dzakwan, M Sabiq; N, Musri Iskandar (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The copyright of recognition for software programmer is needed to improve their productivity. Linux is the right choice of software to use in their fieldwork. The information system is important to help a good service in a laboratory has taken quality competition—the development of technology base on client-servers supporting an expert application maker to get customer satisfaction. The Laboratory information system has developed using gambas 1.014, the databases using MySQL server five, and Linux operating system.